Assessment of a Biosafety Device to Control Contamination by Airborne Transmission during Orthodontic/Dental Procedures - Josilene Santa Rita de Assis; Aguinaldo Silva Garcez; Hideo Suzuki; Victor Angelo Martins Montalli; Denise Nami Fujii; Michelle Bertini Prouvot; Selly Sayuri Suzuki (International Journal of Dentistry)
During the COVID-19 pandemic, dental professionals have faced high risk of airborne contamination between dentists, staff, and patients. The objective of this study was to evaluate the effect of an individual biosafety capsule in dentistry (IBCD) on reducing the dispersion of droplets and aerosols during orthodontic treatment and evaluate the clinician and patient’s perception of using the IBCD. For the in-vitro part of the study, aerosol quantification was performed with and without the IBCD, using a nonpathogenic bacterial strain and viral strain in the reservoir and high-speed dental handpiece. Petri dishes with MRS agar were positioned from the head of the equipment at distances of 0.5, 1, and 1.5 m. After 15 minutes of passive aerosol sampling, the dishes were closed and incubated using standard aerobic conditions at 37°C for 48 hours to count colony forming units (CFUs). For the clinical part of the study, a questionnaire was sent to clinicians and patients to understand their perception of orthodontically treat and receive treatment using the barrier. The use of IBCD showed an effective means to reduce the dispersion of bacterial and viral contamination around 99% and 96%, respectively, around the main source of aerosol (p<0.05). Clinical results showed a 97% bacterial reduction during patient’s consultations (p<0.05). The vast majority of clinicians and patients understand the importance of controlling the airborne dispersion to avoid contamination.